2018
DOI: 10.1002/jhet.3238
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel 1,3,4‐Thiadiazolylpyrazolines Compounds Containing Ferrocene

Abstract: The synthesis of 1,3,4‐thiadiazole skeleton compounds exhibiting high fungicidal activities has been demonstrated. Thirteen novel 1,3,4‐thiadiazolyl‐pyrazolines compounds containing ferrocene were designed and synthesized from the ferrocenylchalcones intermediates 3a–3m and the 2‐hydrazino‐5‐phenyl‐1,3,4‐thiadiazole intermediate 8. All compounds were characterized by 1H NMR, 13C NMR, FT‐IR spectra, and HR‐MS, and the structure of one of the new compounds N‐(4‐phenyl‐1,3,4‐thiadiazol‐2‐yl)‐3‐ferrocenyl‐5‐phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…According to Ki values, compound 1 has been found as the most effective compound of series. This study reported synthesis and AChE inhitory potency of the new pyrazoline derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9). The results indicated that compound 1 had the greatest inhibitory potency with both IC50 (1.30 μM) and Ki (0.13±0.004 μM) values.…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…According to Ki values, compound 1 has been found as the most effective compound of series. This study reported synthesis and AChE inhitory potency of the new pyrazoline derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9). The results indicated that compound 1 had the greatest inhibitory potency with both IC50 (1.30 μM) and Ki (0.13±0.004 μM) values.…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 94%
“…2-Pyrazolines are most popular heterocyclic structure in drug design. They have various important biological activities such as as antimicrobial [6], antifungal [7], antimalarial [8], antiinflammatory [9][10], analgesic [10], anti-Alzheimer's disease [11], anti-Parkinson's disease [12], antidepressant [13][14], anticancer [15][16] and monoamine oxidase (MAO) inhibitory activities [17][18]. In recent years, pyrazoline derivatives are shown to have inhibiting or activating effects on several enzymes such as cholinesterases [19], MAOs, and carbonic anhydrases [20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N -oxide and S -oxide derivatives of nitrogen or sulfur-bearing heterocycles are typical examples of materials used in these reactions. 2 Furthermore, the great attention paid to POCl 3 stems from its diverse applications in chlorination, 3 dehydration, 4 Bischler–Napieralski cyclization, 5 and Vilsmeier–Haack formylation. 6 Dihydroxy-4-oxo-indeno[1,2- b ]pyrroles possessing two vicinal hydroxyl groups have been deoxygenated by reagents such as triphenylphosphine (route A in Scheme 1 ), 7 thionyl chloride, 8 and tetraalkylthionylamides ((NR 2 ) 2 SO) (route B in Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%